Report on the Phytoplankton Pigments measured during the JARE-30 Cruise to Syowa Station, Antarctica, November 1988 to March 1989 - Watanuki, Yutaka; Suzuki, Toshikazu; Fukuchi, Mitsuo (National Institute of Polar Research, 1996)
P(論文) departmental bulletin paper